A Novel, Integrated Cognitive-Behavioral Therapy for Co-Occurring Posttraumatic Stress and Substance Use Disorders: A Case Study - Vujanovic, Anka A. (Cogn Behav Pract, 2018)
Posttraumatic stress disorder (PTSD) and substance use disorders (SUD) are complex psychiatric conditions that commonly co-occur. No preferred, evidence-based treatments for PTSD/SUD comorbidity are presently available. Promising integrated treatments have combined prolonged exposure therapy with cognitive-behavioral relapse prevention therapy for SUD. We describe a case study that showcases a novel, integrated cognitive-behavioral treatment approach for PTSD/SUD, entitled Treatment of Integrated Posttraumatic Stress and Substance Use (TIPSS). The TIPSS program integrates cognitive processing therapy with cognitive-behavioral therapy for SUD for the treatment of co-occurring PTSD/SUD. The present case report, based upon a woman with PTSD comorbid with both cocaine and alcohol dependence, demonstrates that TIPSS has the potential to effectively reduce PTSD symptoms as well as substance use.